Navigated Intraoperative 3D Ultrasound in Glioblastoma Surgery: Analysis of Imaging Features and Impact on Extent of Resection - Saß, Benjamin; Zivkovic, Darko; Pojskic, Mirza; Nimsky, Christopher; Bopp, Miriam H. A. (Frontiers in Neuroscience, 2022)
Background: Neuronavigation is routinely used in glioblastoma surgery, but its accuracy decreases during the operative procedure due to brain shift, which can be addressed utilizing intraoperative imaging. Intraoperative ultrasound (iUS) is widely available, offers excellent live imaging, and can be fully integrated into modern navigational systems. Here we analyze the imaging features of navigated i3D US and its impact on the extent of resection in glioblastoma surgery. Methods: Datasets of 31 glioblastoma resection procedures were evaluated. Patient registration was established using intraoperative computed tomography (iCT). Preoperative MRI (preMRI) and pre-resectional ultrasound (preUS) datasets were compared regarding segmented tumor volume, spatial overlap (Dice coefficient), the Euclidean distance of the geometric center of gravity (CoG), and the Hausdorff distance. Postresectional ultrasound (postUS) and postoperative MRI (postMRI) tumor volumes were analyzed and categorized into subtotal resection (STR) or gross total resection (GTR) cases. Results: The mean patient age was 59.3 ± 11.9 years. There was no significant difference in preresectional segmented tumor volumes (preMRI: 24.2 ± 22.3 cm3; preUS: 24.0 ± 21.8 cm3). The Dice coefficient was of 0.71 ± 0.21, the Euclidean distance of the CoG was 3.9 ± 3.0 mm, and the Hausdorff distance was 12.2 ± 6.9 mm. 18 cases were categorized as GTR, ten cases were concordantly classified as STR on MRI and ultrasound, three cases had to be excluded from postresectional analysis. In four cases i3D US triggered further resection. Conclusion: Navigated i3D US is a reliably adjunct in a multimodal navigational setup for glioblastoma resection. Tumor segmentations revealed similar results in i3D US and MRI, demonstrating the capability of i3D US to delineate tumor boundaries. Additionally, i3D US has a positive influence on the extent of resection, allows live imaging, and depicts brain shift.